ISO-THES: Enlarging Skos through the thesaurus standard ISO 25964 - Pastor-Sánchez, Juan-Antonio (Anuario ThinkEPI, 2013)
The publication of the new ISO 25964 thesaurus standard has coincided with a high level of deployment of the Skos ontology developed by the W3C and should solve the problem posed by the differences between them. There are currently works in progress to create a Skos extension that would use many of the functions provided by the data model of the new standard.
Keywords: ISO 25964; ISO-THES; Thesauri; Skos.